2018
DOI: 10.1007/s11785-018-0822-5
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous 2-Shifts

Abstract: The classification of homogeneous scalar weighted shifts is known. Recently, Korányi obtained a large class of inequivalent irreducible homogeneous bi-lateral 2-by-2 block shifts. In this paper, we construct two distinct classes of examples not in the list of Korányi. It is then shown that these new examples of irreducible homogeneous bi-lateral 2-by-2 block shifts, together with the ones found earlier by Korányi, account for every unitarily inequivalent irreducible homogeneous bi-lateral 2-by-2 block shift.20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…1 2 } n∈Z , 0 < a, b < 1 and a = b. Afterward, S. Hazra [20] also found two classes of irreducible homogeneous bilateral 2by-2 shifts, one of which has the structure shown above. It was also shown that these three classes of operators are mutually unitarily inequivalent when the parameter α > 0.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…1 2 } n∈Z , 0 < a, b < 1 and a = b. Afterward, S. Hazra [20] also found two classes of irreducible homogeneous bilateral 2by-2 shifts, one of which has the structure shown above. It was also shown that these three classes of operators are mutually unitarily inequivalent when the parameter α > 0.…”
Section: Introductionmentioning
confidence: 91%
“…When dim W n = 1, T is called a shift operator. In this case, if W n = span{e n }, then {e n } n∈I is the orthonormal basis of H. A. Korányi and S. Hazra found three large classes irreducible bilateral block shifts in [20,31]. B. Bagchi and G. Misra proved that any irreducible homogeneous operator is a block shift in [1].…”
Section: Irreducibility Of Weighted Block Shift Operatorsmentioning
confidence: 99%
“…The class of homogeneous operators has been studied in a number of articles [2,1,6,7,14,10,18]. It is known that an irreducible homogeneous operator T acting on a Hilbert space H is a block shift, specifically, H is the orthogonal direct sum of subspaces V n , n ∈ I, where I is either the set of a) integers, b) non-negative integers, or c) non-positive integers, such that…”
Section: Introductionmentioning
confidence: 99%
“…All irreducible homogeneous operators, for which dimV n ≤ 1 as well as dimV n ≤ 2, have been classified in [2] and [18], respectively. The classification, in general, of irreducible homogeneous operators in the Cowen-Douglas class over D has been completed (cf.…”
Section: Introductionmentioning
confidence: 99%